On the Zitterbewegung Transient Regime in a Coarse-Grained Space-Time - Weberszpil, José; Helayël-Neto, J. A. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In the present contribution, by studying a fractional version of Diracs equation for the electron, we show that the phenomenon of Zitterbewegung in a coarse-grained medium exhibits a transient oscillatory behavior, rather than a purely oscillatory regime, as it occurs in the integer case, . Our result suggests that, in such systems, the Zitterbewegung-type term related to a trembling motion of a quasiparticle is tamed by its complex interactions with other particles and the medium. This can justify the difficulties in the observation of this interesting phenomenon. The possibility that the Zitterbewegung be accompanied by a damping factor supports the viewpoint of particle substructures in Quantum Mechanics.